Effect of stock market development on long-run economic growth-case of South Africa - Tinavapi, Cuthbert Tafadzwa (Research of GSB, 2017)
This paper examines the long-run causal relationship between stock market development (Johannesburg Stock Exchange) and economic growth in South Africa by making use of the Autoregressive Distributed Lag Bounds method. The study also reviews South Africa's economic growth trajectory using World Bank data sets over the period between 1975 and 2013. Stock market development is proxied by stock market capitalization, stock market value traded and stock market turnover and economic growth is represented by gross domestic product (GDP). The study is predicated on the the puzzle of why there is such a large disparity between the economic growth rate experienced by South Africa and its peers in spite of South Africa having a world leading stock market in the form of the Johannesburg Stock Exchange? The study presupposes that a causal relationship between stock market development and economic growth exists in South Africa and questions why the effects thereof are not more emphatic. The purpose of the study is to seek answers to the question of whether there is a significant and positive correlation between the development of the Johannesburg Stock Exchange and economic growth in post-apartheid South Africa. The study would also examine and describe the economic growth trajectory of South Africa look prior to 1994 and post 1994. The study makes use of annual time series data, which covers the period from 1975 to 2013 obtained from different sources, including South African Reserve Bank annual reports, quarterly bulletins, International Financial Statistics (IFS) from the International Monetary Fund and World Bank Statistical Yearbook. In addition, data on real GDP growth rate for South Africa was obtained from Statistics South Africa whilst the Johannesburg Stock Exchange's stock market capitalization and total value of stocks traded was obtained from the Johannesburg Stock Exchange website, turnover ratio of stocks traded was calculated. To accomplish the goal of this study, the autoregressive distributed lag (ARDL) methodology was employed with consideration of the existence of a structural break in the series due to the study considering the pre and post-apartheid eras in South Africa. The existence of a long-run relationship between the variables was tested after using lag length selection criteria from an estimated vector autoregression to select the optimal lags for the vector error correction model of the ARDL. The results obtained from the analysis confirmed that there is a long-run positive relationship between economic growth, stock market capitalization and stock market traded value. The existence of a positive long-run relationship between economic growth and two of the three proxies for stock market development can be used to make a general inference of a positive long-run relationship between the development of the JSE and South Africa's growth rate post-apartheid. The empirical analysis further confirmed that the growth elasticity between stock market capitalization, stock market traded value and economic growth is less than 1 indicating a possible channelling of funds raised on the JSE to offshore investments or to nonproductive sectors of the economy. It was also evident from regression analyses run on the post democracy era that post-apartheid South Africa has only had a positive statistically significant effect on the domestic stock market capitalization at the exclusion of stock market value traded and stock market turnover. The results of this study show that stock market development Granger-causes economic growth.